2013
DOI: 10.1016/j.jbiotec.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Lipases efficiently stearate and cutinases acetylate the surface of arabinoxylan films

Abstract: This is the first report on successful enzyme catalyzed surface esterification of hemicellulose films. Enzyme catalyzed surface acetylation with vinyl acetate and stearation with vinyl stearate were studied on rye arabinoxylan (AX) films. Different surface analytical techniques (FT-IR, TOF-SIMS, ESCA, CA) show that lipases from Mucor javanicus, Rhizopus oryzae and Candida rugosa successfully surface stearate AX films and that a cutinase from Fusarium solani pisi surface acetylates these films. The specificitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…From 1 H NMR data presented in Table 4, the polymerization conversion rate of poly(ethylene adipate) (Scheme A') was twice higher than that of poly(ethylene succinate) (Scheme B'). This can be attributed to the alkyl chain length selectivity of lipases, which presented higher activity towards long alkyl chain substrate, dimethyl adipate, than towards dimethyl succinate [30,31]. 1 H NMR data of poly(ethylene adipate) (Scheme A') ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From 1 H NMR data presented in Table 4, the polymerization conversion rate of poly(ethylene adipate) (Scheme A') was twice higher than that of poly(ethylene succinate) (Scheme B'). This can be attributed to the alkyl chain length selectivity of lipases, which presented higher activity towards long alkyl chain substrate, dimethyl adipate, than towards dimethyl succinate [30,31]. 1 H NMR data of poly(ethylene adipate) (Scheme A') ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, lipase was used to connect laurate alkyl chains to cellulose nanocrystals with the formation of ester linkages under aqueous conditions (Yin et al 2020). Stepan et al (2013) earlier had demonstrated the attachment of stearate groups to hemicellulose in the presence of lipase. An aqueous enzymatic derivatization of ethylcellulose with poly-hydroxybutyrate chains had been reported by Iqbal et al (2014).…”
Section: Enzymaticmentioning
confidence: 99%
“…The enzymatic esterification of Avicel and cotton cellulose was reported using wild‐type cutinase from Fusarium solani and an engineered cutinase, fused with the carbohydrate‐binding module N1 from Cellolomonas fimi . The surface esterification of hemicellulose films catalyzed by lipases from Mucor javanicus , Rhizopus oryzae , Candida rugosa and by a cutinase from F. solani pisi is reported by others . The specificities of cutinase and lipases were compared.…”
Section: Introductionmentioning
confidence: 97%
“…The surface esterification of hemicellulose films catalyzed by lipases from Mucor javanicus, Rhizopus oryzae, Candida rugosa and by a cutinase from F. solani pisi is reported by others. 10 The specificities of cutinase and lipases were compared. Lipase presented higher activity toward long alkyl chain substrates while cutinase presented higher activity toward shorter alkyl chain substrates.…”
Section: Introductionmentioning
confidence: 99%